The profit efficiency analysis of malaysian commercial banks: A Data Envelopment Analysis (DEA) - Nursyazfaliana Mohd Arif; Ayunazira Nasir; Rakin Syuwari Rodrigo; Imbarine Bujang; Siti Julea Supar (goodwood publishing, 2023)
Purpose: This study aims to measure and compare the profit efficiency of local and international commercial banks in Malaysia before and during the COVID-19 pandemic in accordance with the new Basel Committee III guidelines, which mandate banks to adopt a systematic approach to deal with uncertain economic conditions, including events such as the COVID-19 pandemic. Research methodology: This study uses Data Envelopment Analysis (DEA), a non-parametric method based on linear mathematical programming, to measure the efficiency of local and international commercial banks in Malaysia. Results: The analysis revealed that local international commercial banks were more efficient than local commercial banks before and during the COVID-19 crisis. Limitations: Potential areas for future research involve extending the application of Data Envelopment Analysis (DEA) and examining various dimensions and metrics about different countries, as each country possesses distinct financial contexts. Contribution: This study contributes to the existing body of literature on the profit efficiency of local and international banks. It provides insights that can assist the government in formulating appropriate regulations to enhance banks’ profit efficiency, thereby improving their overall performance.